DESIGN OF FIR QMF BANK USING WINDOWING FUNCTIONS - Kamislioglu, Bircan; Karaboga, Nurhan (Ieee, 2014)
The past over the years, single or multi-dimensional signal processing applications, communication systems, biomedical signal processing, word coding, sub-band coding in applications such as efficient use filter banks; single filter instead of multiple custom filters come together with being designed. In this study, two-channel filter banks a special case known as the QMF (Quadrature Mirror Filter - Quarter-mirror filter) bank for the design of Kaiser, Chebyshev and Hanning windowing methods with the filter's cutoff frequency frequency on the optimization of a design based were made. QMF bank design, failure to peak reconstruction error (Peak Reconstruction Error-PRA) is based. As a result of the ongoing applications designed filter banks belonging to the numerical results and comparisons are given.
22nd IEEE Signal Processing and Communications Applications Conference (SIU) -- APR 23-25, 2014 -- Karadeniz Teknik Univ, Trabzon, TURKEY
Keywords: Filters; Domain